Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]

Investigation of wustite (Fe1-xO) by femtosecond laser assisted atom probe tomography - Bachhav, Mukesh N.; Danoix, R.; Danoix, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Vurpillot, F. (Ultramicroscopy, 2011)
In this paper, we report results obtained from laser assisted three-dimensional (3-D) atom probe tomography (APT) on wustite (Fe1-xO). Oxides are generally insulating and hence hard to analyse in conventional electrical assisted APT. To overcome this problem, femtosecond laser pulses are used instead of voltage pulses. Here we discuss some aspects of pulsed laser field evaporation and optimization of parameters to achieve better chemical accuracy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atom probe tomography; Laser assisted field evaporation; Wustite